Ensino fundamental e as relações de sociabilidades: os adolescentes e a diversidade na escola - SANTOS, Patrícia Simith dos (2020)
This paper aims to analyze the social relations established among 175 (one hundred and seventy five) teenagers, in two public elementary schools of Belém - PA. For the intended analysis, we will use the conceptual notions of symbolic violence, hierarchy and habitus, in Pierre Bourdieu (1996, 2002, 2010), and representation, in Roger Chartier (1991, 1982). Regarding the specialized literature on social relations, teenager sociabilities and racial ethnic relations, we will adopt the formulations of Nicelma Soares (2010), Wilma Coelho; Mauro Coelho (2016), Wilma Coelho; Carlos Silva (2015; 2017; 2018; 2019). The conceptual formulations of Laurence Bardin (2010), Marli André (2003) and Heraldo Vianna (2003), that helped in the treatment and data label, school ethnography and observations. We deduce that students have, in social networks, the centrality of their attention, including in establishing and breaking social relations. The centrality of attention on social networks takes on the focus of interest of the school experience, whose content conveyed through it, takes a secondary place against social networks, because these students think about the current day The pedagogical investments of the school differ from the interests demanded by the students.